2017
DOI: 10.1634/theoncologist.2016-0456
|View full text |Cite
|
Sign up to set email alerts
|

Management of Treatment-Related Adverse Events with Agents Targeting the MAPK Pathway in Patients with Metastatic Melanoma

Abstract: Targeted therapy with BRAF plus MEK inhibitors has become the standard of care for patients with advanced-stage V600-mutant metastatic melanoma. To provide optimal therapeutic benefit to patients, clinicians need a keen understanding of the toxicity profiles of these drugs. Prompt identification and an understanding of which adverse events are most likely BRAF or MEK inhibitor associated provide a rationale for appropriate therapy adjustments. Practical recommendations derived from clinical experience are prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 52 publications
2
57
0
2
Order By: Relevance
“…6,7 LVEF-D induced by BRAF and MEKis, although widely reported in clinical trials, has never been thoroughly described to date and data regarding its management are limited. [8][9][10] The main objective of the study presented herein was therefore to describe the characteristics of LVEF-D in a large cohort of metastatic melanoma patients treated with BRAF and/or MEKis in a real-life setting. Secondary objectives were to determine whether laboratory, electrocardiogram (ECG) or transthoracic echocardiography (TTE) markers could identify sub-clinical cardiac damage and be predictive of a LVEF-D.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 LVEF-D induced by BRAF and MEKis, although widely reported in clinical trials, has never been thoroughly described to date and data regarding its management are limited. [8][9][10] The main objective of the study presented herein was therefore to describe the characteristics of LVEF-D in a large cohort of metastatic melanoma patients treated with BRAF and/or MEKis in a real-life setting. Secondary objectives were to determine whether laboratory, electrocardiogram (ECG) or transthoracic echocardiography (TTE) markers could identify sub-clinical cardiac damage and be predictive of a LVEF-D.…”
Section: Introductionmentioning
confidence: 99%
“…18 26,27 To alleviate the BRAFi-induced phototoxicity, we tested a panel of antioxidants as an attempt to find feasible alternatives for the management of phototoxicity. 28,29 Accordingly, the physiological antioxidants vitamin C, vitamin E, trolox, and GSH were added to the 3T3 NRU phototoxicity assay with the BRAFi vemurafenib, dabrafenib, and encorafenib. Interestingly, we observed that high-dose GSH was able to fully rescue the UVA-induced phototoxicity of vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…On average, fevers last approximately 9 days. Generally, half of patients who experience pyrexia have recurrent events that typically last 4–5 days .…”
Section: Adverse Events and Managementmentioning
confidence: 99%
“…Patients should also be encouraged to immediately report fever or related symptoms while undergoing dabrafenib plus trametinib treatment . If pyrexia does occur, the recommended course of action is to rule out infection , although an infectious workup (i.e., complete blood count, comprehensive metabolic panel, and blood and urine cultures) is not recommended if pyrexia is uncomplicated, with no evidence of localizing symptoms . If pyrexia is severe, serum creatinine should be monitored.…”
Section: Adverse Events and Managementmentioning
confidence: 99%
See 1 more Smart Citation